Phenotypic plasticity of blistering ammannia (Ammannia baccifera) in competition with direct-seeded rice - Chauhan, Bhagirath Singh (Cambridge University Press, 2013)
Crop interference and weed-competitive cultivars are a component of integrated weed management, but their use requires understanding the extent to which rice can interfere with weed growth and how weeds may respond to rice interference. Growth of blistering ammannia was studied in a screen house by growing it alone or with rice seeded in rows (20 cm) or broadcast at the rate of 25 and 75 kg ha−1. The growth of blistering ammannia was similar whether grown with rice seeding rates of 25 or 75 kg ha−1or with broadcast or row-seeded rice, suggesting that the weed is a weak competitor if rice is planted uniformly. Rice interference greatly reduced the number of blistering ammannia leaves and leaf, stem, total shoot, and root biomass. However, the weed showed the ability to reduce the effects of rice interference by increasing leaf and stem biomass in the upper half of the plant, and increasing specific stem length. At 11 wk after planting, blistering ammannia had 71 to 80% leaf biomass in the upper half of the plant when grown with rice interference compared with only 29% when grown without rice interference. Despite such plasticity, blistering ammannia shoot and root biomass at final harvest decreased by 94 to 99% when grown with rice compared with its biomass without crop interference. These results suggest that blistering ammannia is a poor competitor and uniform rice density could be very effective in suppressing blistering ammannia in direct-seeded rice systems.